Metal-free synthesis of aminomethylated imidazoheterocycles: dual role of tert-butyl hydroperoxide as both an oxidant and a methylene source. Issue 44 (31st October 2018) - Patel, Om P. S.; Nandwana, Nitesh Kumar; Sah, Ajay Kumar; Kumar, Anil
Abstract : A metal-free method is developed for the aminomethylation of imidazoheterocycles with 2/4-aminoheterocycles using TBHP as a carbon source as well as an oxidant. Abstract : A novel and efficient aminomethylation approach has been developed for the regioselective functionalization of imidazoheterocycles under metal-free conditions. A wide range of imidazoheterocycles and 2/4-aminoazaheterocycles successfully provided corresponding aminomethylated imidazoheterocycles in moderate to excellent (33–80%) yields. The isotopic labelling study suggested that TBHP played a dual role as both an oxidant and a methylene source in this transformation. The developed protocol follows a radical pathway which is supported by radical trapping experiments.